Establishment and Management Of COVID-19 Testing Molecular Laboratory in Minimal Resource Setting, Challenges and Issues Reported From Birgunj, Nepal – An Experience of Pathologist (Med Phoenix, 2021)
The Coronavirus pandemic is recording numerous deaths worldwide. The temporal distribution and burden of the disease varies from setting to setting based on economic status, demography and geographic location. Nepal reported the first COVID-19 case on January 23, 2020. A rapid increase in the number of COVID-19 cases was being reported in Nepal as of June 2020. Limited molecular laboratory capacity in resource limited settings is a challenge in the diagnosis of the ever-increasing cases and the overall management of the disease. In this article, we share the experience, challenges and prospects in the rapid establishment of  COVID-19 testing laboratory in Birgunj from available resources. We provide empirical evidence from Parsa district, as this is one of the SARS-CoV-2 transmission hotspots in Nepal and it  is likely generalizable to other similar settings in the country. The first step in establishing the COVID-19 molecular testing laboratory were i) identifying a suitable space ii) renovating it and iii) mobilizing materials including consumables, mainly from the hospital store and administration. A chain of experimental design was set up with distinct laboratories to standardize the extraction of samples, preparation of the master mix and detection. At the commencement of sample reception and testing, laboratory contamination was among the primary challenges faced. The source of the contamination was identified in the master mix room and resolved. In summary, the established COVID-19 testing lab (Narayani PCR Lab) has tested more than 40,000 samples (January 2021) and is now the preferred setting for CoVID-19 testing. The lessons learnt may benefit the further establishment of testing laboratories for COVID-19 and/or other epidemic/pandemic diseases in resource-limited settings.